Laboulbeniales (Fungi: Ascomycota) infection of bat flies (Diptera: Nycteribiidae) from Miniopterus schreibersii across Europe - Szentiványi, Tamara (Parasit Vectors, 2018)
BACKGROUND: Bat flies (Diptera: Nycteribiidae and Streblidae) are obligate, blood-sucking ectoparasites of bats with specialized morphology, life-cycle and ecology. Bat flies are occasionally infected by different species of Laboulbeniales (Fungi: Ascomycota), microscopic fungal ectoparasites belonging to three genera: Arthrorynchus spp. are restricted to the Eastern Hemisphere, while species of Gloeandromyces and Nycteromyces occur on Neotropical bat flies. Little is known about the distribution and host specificity of Arthrorynchus spp. on bat flies. In this study, we focused on sampling bat flies from the cave-dwelling bat species Miniopterus schreibersii. Bat and ectoparasite collection took place in Albania, Croatia, Hungary, Italy, Portugal, Slovakia, Spain and Switzerland. Flies were inspected for Laboulbeniales infections. RESULTS: Six hundred sixty seven bat flies of five species were collected: Nycteribia latreillii, N. pedicularia, N. schmidlii, Penicillidia conspicua, and P. dufourii. Laboulbeniales infection was observed on 60 specimens (prevalence = 9%). Two Laboulbeniales species, Arthrorhynchus eucampsipodae and A. nycteribiae, were present on three bat fly species. All observations of A. eucampsipodae were on N. schmidlii, and A. nycteribiae was present on P. conspicua and P dufourii. Arthrorhynchus eucampsipodae is, for the first time, reported from Slovakia and Spain. Arthrorhynchus nycteribiae represents a new country record for Portugal and Slovakia. There were no significant differences among infection rates in different countries. Females of N. schmidlii showed a higher infection rate than males with an observable trend (P = 0.0502). No sex differences in infection rate for P. conspicua and P. dufourii were detected. Finally, thallus density was significantly lower in N. schmidlii compared to P. conspicua and P. dufourii. CONCLUSIONS: With this study, we contribute to the knowledge of the geographical distribution and host specificity of Laboulbeniales fungi associated with ectoparasitic bat flies within Europe. We discuss parasite prevalence and host specificity in the light of our findings and the available literature. Penicillidia conspicua is unambiguously the main host species for A. nycteribiae based on our and previous findings. Differences in parasite intensity and sex-biased infections of the fungi are possible depending on the species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-018-2921-6) contains supplementary material, which is available to authorized users.